VISUALISASI DATA DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN R STUDIO DI SMK INFORMATIKA TULANGAN SIDOARJO - Alfisyahrina Hapsery; Wara Pramesti; Khusnul Khotimah; Abdullah Jabbar Daimuddin (STKIP PGRI Sidoarjo, 2022)
The development of technology has brought significant changes to various circles. Minimal knowledge of computing in the field of data science is the main reason for the Lecturer of the UNIPA Surabaya Statistics Study Program to introduce and train teachers about programming languages using R Studio. Based on the needs of the Informatics Vocational School Teachers of Reinforcement Science for their special programming language R Studio, the Statistics Study Program lecturers conducted an introduction in the form of training. The training consists of three stages of the procedure. Starting from material explanations, workshops, and simulations. The existing problems are in the introduction and processing of the R Studio programming language which supports the Big Data and Industry 4.0 era. This service program provides technology solutions and data processing using the R Studio programming language for data visualization. Explanation of the material presented by the resource person is in accordance with the needs of the teachers for data visualization using the R Studio programming language. Materials or methods needed in the world of education that support the era of big data, data science, and the MB-KM learning program.